Observations of a fireball in northern Sweden, 18:55UT, 27 February, 2023 - Kero, Johan; Borderes-Motta, Gabriel; Kastinen, Daniel; Sergienko, Tima; Brändström, Urban; Visuri, Jaakko; Gritsevich, Maria; Moilanen, Jarmo; Cardozo Mourão, Daniela; Celi Braga Camargo, Barbara (Swedish Institute of Space Physics, 2026)
* FITS files obtained with the ALIS_4D and PNG files of the plots of the frames (50-150) of each FITS file.
The data are organized by observing station and correspond to optical detections used in the analysis
presented in the associated publication.

* Optical parameter used in the image analysis and a summary plot of star calibration errors.

* Wind data extracted from the Global Forecast System (GFS) model and stored in CSV format.
The file includes wind components and/or wind speed and direction for a selected geographic region and time period.
The wind data were obtained from publicly available GFS products provided by the National Centers for Environmental Prediction (NCEP/NOAA).

* Image data from a Swedish meteor camera located in Abisko, Sweden.

* Image data from a Finnish meteor observer located in Kittilä, Finland.

* FITS-filer erhållna med ALIS_4D samt PNG-filer genererade från bildrutorna (50–150) i varje FITS-fil. Datat är uppdelat efter observationsstation och motsvarar de optiska detektioner som användes i analysen som presenteras i den tillhörande publikationen.

* Optiska parametrar som användes i bildanalysen samt en sammanfattande figur över fel i stjärnkalibreringen.

* Vinddata extraherade från modellen Global Forecast System (GFS) och lagrade i CSV-format. Filen innehåller vindkomponenter och/eller vindhastighet och vindriktning för ett valt geografiskt område och en vald tidsperiod.
Vinddata erhölls från offentligt tillgängliga GFS-produkter tillhandahållna av National Centers for Environmental Prediction (NCEP/NOAA).

* Bilddata från en svensk meteorkamera placerad i Abisko, Sverige.

* Bilddata från en finsk meteorobservatör i Kittilä, Finland.
Observationer av ett eldklot i norra Sverige, 18:55UT, 27 februari, 2023
Keywords: METEORITE ORIGIN; meteors; meteorer; bolides; meteorite parent bodies; meteoroids; Natural Sciences; Naturvetenskap; Physical Sciences; Fysik; Fusion, Plasma and Space Physics; Fusion, plasma och rymdfysik; Geophysics; Geofysik; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap